Coronal Pulpotomy Technique Analysis as an Alternative to Pulpectomy for Preserving the Tooth Vitality, in the Context of Tissue Regeneration: A Correlated Clinical Study across 4 Adult Permanent Molars - Raji Viola Solomon; Umrana Faizuddin; Parupalli Karunakar; Grandhala Deepthi Sarvani; Sevvana Sree Soumya (Case Reports in Dentistry)
Aim. (1) The aim of the clinical study revolves around the accurate diagnosis, proper case selection, and the management of acute irreversible pulpitis in permanent molars with closed apices using conservative and economical treatment modalities like vital pulpotomies with regenerative approaches over conventional root canal procedures. (2) To evaluate the use of autologous substances such as platelet concentrates and calcium silicate based materials in promoting the healing and regeneration of the inflamed pulp. Summary. Vital pulpotomy was performed on 5 carious involved, permanent molars diagnosed with acute irreversible pulpitis in 17- to 22-year-old patients. Taking into consideration the patient’s age and the condition of the underlying pulp tissue, PRF pulpotomy was planned in view of preserving the vitality of the intact radicular pulps. Regenerative procedures with second generation blood matrices were chosen to encourage the recovery of the inflamed pulps. The systematic follow-up examinations performed at 3, 6, 9, 12, 18, 22, and 24 months revealed a successful clinical and radiological outcome. Within the limits of the present clinical study and correlating the success across the treated clinical cases, we safely conclude the potential scope of regenerative pulpotomy approaches in acute irreversible pulpitis in adult permanent teeth.